Pelatihan Citation dan Reference Manager dengan Menggunakan Mendeley - Sakina, Rahma (Ma'soem University, 2022)
This research aims at giving information and comprehension to undergraduate students of various study programs and universities in West Java about the rules of citation and reference manager by using Mendeley. This activity was held as an attempt to promote students’ paper quality which can be seen from its content and references. This activity was collaborated with Rafredu institution and was held online through Zoom Meeting. The method of this community service is Asset Based Community Development. The results show that the participants are able to understand the materials well and most of them are able to write down citation and references correctly by using Mendeley.